Konsep Ilmu dalam Perspektif Islam: The Concept of Science in Islamic Perspective - Azfaruddin, Muhammad Farid; Rasyid, Abdullah; Mauludiyah, Lilik; Mustofa, Muhammad Lutfi (University of Darussalam Gontor, Indonesia, 2024)
The study of knowledge in Islam is very important. Knowledge in modern times is considered lacking in explaining phenomena in this era. The purpose of writing this article is to analyze the Islamic perspective on science, including the concepts, classifications, and roots of science. This research method is qualitative with a literature study approach originating from e-journals, books and trusted media. The results of this study state that first, the concept of science according to Islam does not only discuss physical aspects, but also metaphysical aspects. Science must also have objectivity, meaning that it can be accepted by many people and not be influenced by individual thoughts. Second, Islam broadly classifies knowledge into two, namely fardu ain knowledge and fardu kifayah knowledge. Figures of Muslim scientists such as Al-Farabi and Ibn Nadhim divided world knowledge into more detail. Third, Knowledge in Islam comes from the Al-Qur'an, Hadith, intellect, and intuition. How to obtain this knowledge can be through revelation, five senses, reason, and heart or intuition. Fourth, Modern science in the West began to develop, and Western society relinquished the influence of the church to adopt a modern way of thinking that emphasized rationality and empirical evidence. Western thought considers religion and science to be separate, viewing this division as a hindrance to progress. However, in the Islamic tradition, religious and secular powers are not divided